Conservation biogeography in the Mexican Mountain Component: bridging conservation and patterns of endemism - Morales, Ricardo; Escalante, Tania; Noguera-Urbano, Elkin A.; Gámez, Niza; Rodríguez-Tapia, Gerardo (THERYA, 2016)
The Mexican Mountain Component (MMC) includes six biogeographical provinces. In this manuscript, we propose to use endemic taxa as surrogates to prioritize for conservation areas of the MMC. We use the distribution of 24 endemic mammals to prioritize conservation sites in the MMC and to evaluate the current Mexican system of protected natural areas (PNA). We used species distribution models and the software ConsNet 2.0 to prioritize areas for conservation, evaluating two algorithms (the representation maximization problem, and the area minimization problem) and two different representation targets (10 % and 25 %) of the distributional area of endemic taxa. In addition, we considered the effects of including existing PNA and/or excluding areas with altered vegetation. The representation maximization problem including current PNA was ineffective for reaching conservation targets. Meanwhile, all area minimization problems allowed us to prioritize areas reaching the targets of surrogates. In particular, a strategy that considers area minimization problem using a target of 10 % of the distribution of surrogates, including PNA and excluding the altered vegetation, was the most favorable for maintaining the distributional patterns of the endemic mammals. This solution proposes the protection of a total of 37,460 km2, covering areas with altitude above 2,400 m located mainly in the Sierra Madre Occidental, the Transmexican Volcanic Belt, and provinces of the Sierra Madre del Sur. A prioritization strategy based on the distribution of endemic mammals as surrogates can help to maintain the distributional patterns of endemism of the Mexican biota. Key words: conservation biogeography; endemicity; mammals; Mexico; surrogates; sympatry.